(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
This research aimed to investigate the theme of burnout syndrome in high school teachers. In particular, the objective was to verify if the five personality traits can be considered predictors of the four dimensions of burnout. The sample consisted of 171 teachers, 49 males and 122 females. For the burnout measurement, the Link Burnout Questionnaire (LBQ) was used, and for the personality measure, the Big Five Questionnaire (BFQ) was used. As predictive factors for the development of the negative polarity of Psychophysical Exhaustion, the results identify both Energy and Emotional Stability. For Relational Deterioration, the same traits emerge due to the dimension of Professional Inefficiency. For the LBM’s Disillusion dimension, there was no corresponding predictive BFM trait, but by reducing the statistical error via analysis of regression with fixed effects, Agreeableness and Emotional Stability were predictive. The research confirms the relationship between personality and burnout, but future studies should both analyse the influence exerted by the contextual factors on the onset of the syndrome and deepen the research on the mental models